Hubungan Psikososial, Spiritual, Ekonomi, Dan Riwayat Kontak Terhadap Kejadian TB Di Rumah Sakit Mega Buana Kota Palopo (Window of Public Health Journal, 2025)
The number of new TB cases in 2014-2015 showed an increase in TB. Most deaths from TB can be prevented early with proper diagnosis and treatment. However, there are still many gaps in detection and treatment. Research at Mega Buana Hospital, Palopo City, due to the fluctuating cases of Tuberculosis in 2021, there were 118 positive cases; in 2022, there were 184 cases; in 2023, there were 152 cases. This study is a quantitative study with a cross-sectional approach. The cross-sectional approach is a research method in which measurements or observations are carried out at a particular time without involving intervention or continuous observation of the research subjects. The sampling technique in this study was purposive sampling. The study population was all tuberculosis patients at Mega Buana Hospital, and the sample size was 60 respondents. Data was obtained using a questionnaire. The analysis method used was Univariate and bivariate analysis using the chi-square test. The results of this study indicate that psychosocial has no relationship with TB patients at Mega Buana Hospital, Palopo City, in 2024. p-value = 0.181, which means that the p-value> 0.05. spiritual has no relationship with TB patients at Mega Buana Hospital, Palopo City in 2024 p-value = 0.898, which indicates that the p-value> 0.05 economic status has a relationship with TB patients at Mega Buana Hospital, Palopo City in 2024 p-value = 0.000 which means that the p-value